2019
DOI: 10.1016/j.sjbs.2018.11.009
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Codonopis bulleynana Forest ex Diels on chronically constipated mice

Abstract: To verify the laxative effect of Codonopsis bulleyana and its effect on intestinal microbiota, a long-term constipation model was established using 3.0 mg/kg loperamide hydrochloride, after which, the long-term constipation model was administered by 0.2 g/ml high-dose Codonopsis bulleyana water extract. The therapeutic effects were observed by measuring defecation amount and feces moisture content. The composition of intestinal microbiota was detected and analyzed using16S rDNA sequencin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…8,9 An imbalance of intestinal microbiota is one of the major causes of constipation. 47 In this study, we found that gut microbiota had changed greatly in the aged constipated rats, including reduction of intestinal bacterial diversity at the class, order, and genus levels, as well as the abnormalities of 9 gut microbiota. Such changes of gut microbiota lead to chronic constipation in rats.…”
Section: Papermentioning
confidence: 63%
“…8,9 An imbalance of intestinal microbiota is one of the major causes of constipation. 47 In this study, we found that gut microbiota had changed greatly in the aged constipated rats, including reduction of intestinal bacterial diversity at the class, order, and genus levels, as well as the abnormalities of 9 gut microbiota. Such changes of gut microbiota lead to chronic constipation in rats.…”
Section: Papermentioning
confidence: 63%
“…Its water extract acts as a laxative in constipated mice. [108] Superfine powder of Codonopsis safeguards the gastric mucosa in rats with gastric ulcers. [109] Flavonoids from Codonopsis facilitate cell migration in small intestinal epithelial cells, countering the migration inhibition caused by DFMO or 4-AP and potentially increasing cellular arginine through polyamine signaling pathway modulation.…”
Section: Protecting Gastrointestinal Mucosa and Anti-ulcer Effectsmentioning
confidence: 99%
“…Figure 4 illustrates the phenylpropanoids extracted from Codonopsis are primarily composed of tangshenoside I-VI (102-107), [45] 3,4-dihydroxyphenethyl-5-hydroxy-4-oxopentanoate (108) (112), and 3,4-dihydroxyphenylethano1-8-O-[β-d-apiofuranosyl (1→2)]-β-d-glucopyranoside (113). [46] Additionally, newly identified compounds include tangshenoside VIII (114), syringin (115), [47] methlysyringin (116), [48] lanceolune A-C (117-119), [49] cordifoliketone A-B (120-121), [50] ethylsyringin (122), [27] codonoside A (123), codonoside B (124), [51] and coniferoside (125).…”
Section: Phenylpropanoidsmentioning
confidence: 99%
“…This condition will affect changes in the composition of microbiota diversity, where the number of harmful bacteria (such as Fusobacterium) will increase. In contrast, the number of good bacteria (such as Bifidobacterium, Bacteroides, and Lactobacillus) will decrease (Luan et al, 2019). Measuring the weight of wet feces per day is the indicator most often used to assess the presence or absence of constipation in individuals.…”
Section: Irritable Bowel Syndrome (Ibs)mentioning
confidence: 99%
“…Measuring the weight of wet feces per day is the indicator most often used to assess the presence or absence of constipation in individuals. Normal feces weigh around 150 g/day, and the bacteria in the feces are more diverse in normal mice (Cummings et al, 1992;Luan et al, 2019).…”
Section: Irritable Bowel Syndrome (Ibs)mentioning
confidence: 99%